The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1158/1535-7163.mct-06-0266
|View full text |Cite
|
Sign up to set email alerts
|

Prodigiosin induces the proapoptotic gene NAG-1 via glycogen synthase kinase-3β activity in human breast cancer cells

Abstract: Prodigiosin (2-methyl-3-pentyl-6-methoxyprodigiosene) is a bacterial metabolite that has anticancer and antimetastatic properties. However, the molecular mechanisms responsible for these abilities are not fully understood. Gene expression profiling of the human breast cancer cell line MCF-7 treated with prodigiosin was analyzed by cDNA array technology. The majority of the significantly modified genes were related to apoptosis, cell cycle, cellular adhesion, or transcription regulation. The dramatic increase o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 36 publications
(35 reference statements)
4
51
0
Order By: Relevance
“…The reason why we were interested in studying NAG-1 as a molecular drug target was because of the previous reports that anticancer drugs could induce apoptosis by causing Akt dephosphorylation and glycogen synthase kinase (GSK) 3b activation, which eventually modulate NAG-1 upregulation-a proposed Akt/ GSK3b/NAG-1 pathway. 33,34 We had actually shown that AST treatment for 6-72 hr induces phospho-GSK3b overexpression in HT-29 cells time-dependently (Supporting Information Fig. 2), which is consistent with the upregulation of NAG-1.…”
Section: Discussionsupporting
confidence: 73%
“…The reason why we were interested in studying NAG-1 as a molecular drug target was because of the previous reports that anticancer drugs could induce apoptosis by causing Akt dephosphorylation and glycogen synthase kinase (GSK) 3b activation, which eventually modulate NAG-1 upregulation-a proposed Akt/ GSK3b/NAG-1 pathway. 33,34 We had actually shown that AST treatment for 6-72 hr induces phospho-GSK3b overexpression in HT-29 cells time-dependently (Supporting Information Fig. 2), which is consistent with the upregulation of NAG-1.…”
Section: Discussionsupporting
confidence: 73%
“…Given the importance of Wnt/β-catenin signaling in the development of human cancers (1-4), the Wnt inhibitory function of prodigiosin may be attributed to its selective cytotoxicity toward cancer cells. A previous study noted that prodigiosin-induced apoptosis could be blocked by GSK3β pharmacologic inactivation, suggesting that prodigiosin may mediate GSK3β activation (17). In this study, we have demonstrated that prodigiosin can reduce GSK3β phosphorylation at Ser9, leading to the increased activity of GSK3β.…”
Section: Discussionsupporting
confidence: 59%
“…A previous study indicated that pharmacologic inhibitors of GSK3β could prevent prodigiosin toxicity (17). Thus, we evaluated the effect of prodigiosin on the phosphorylation state of GSK3β, a serine/threonine kinase involved in various cellular responses, including regulation of β-catenin stability.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The National Cancer Institute (dtp.nci.nih.gov) tested prodigiosin (and some of its derivates) against a collection of ~ 60 cell lines with an average IC 50 (for PG) of 2.1 µM (1). It has been described that the apoptotic process triggered by PG is mediated through the mitochondrial pathway and involves the induction of the proapoptotic gene NAG-1 (2). Nevertheless, the molecular target of this agent is still unknown.…”
Section: Introductionmentioning
confidence: 99%